Inactivation of the tumor suppressor WTX in a subset of pediatric tumors. Issue 1 (5th November 2013) - Akhavanfard, Sara; Vargas, Sara O.; Han, Moonjoo; Nitta, Mai; Chang, Clarice B.; Le, Long P.; Fazlollahi, Ladan; Nguyen, Quan; Ma, Yunqing; Cosper, Arjola; Dias‐Santagata, Dora; Han, Jae Y.; et al.
<x xml:space="preserve">Abstract</x> WTX is a tumor suppressor gene expressed during embryonic development and inactivated in 20–30% of cases of Wilms tumor, the most common pediatric kidney cancer. WTX has been implicated in several cellular processes including Wnt signaling, WT1 transcription, NRF2 degradation, and p53 function. Given that WTX is widely expressed during embryonic development and has been recently shown to regulate mesenchymal precursor cells in several organs, we tested for the potential involvement of WTX in a panel of pediatric tumors and adult sarcomas. A total of 353 tumors were screened for WTX deletions by fluorescence in situ hybridization (FISH). Discrete somatic WTX deletions were identified in two cases, one hepatoblastoma and one embryonal rhabdomyosarcoma, and confirmed by array comparative genomic hybridization. Direct sequencing of the full WTX open reading frame in 24 hepatoblastomas and 21 embryonal rhabdomyosarcomas did not identify additional mutations in these tumor types. The presence of WTX mRNA was confirmed in hepatoblastomas and embryonal rhabdomyosarcomas without WTX deletions by RNA‐in situ hybridization. Notably, tumors with evidence of WTX inactivation, Wilms tumor, hepatoblastoma and rhabdomyosarcoma, are primitive tumors that resemble undifferentiated precursor cells and are linked to overgrowth syndromes. These results indicate that WTX inactivation occurs in a wider variety of tumor types than previously appreciated and point to shared pathogenic mechanisms between a subset of pediatric malignancies. © 2013 Wiley Periodicals, Inc.